Peridynamic simulation of permafrost thawing around an inclined mine working - Semin, Mikhail (Frontiers in Mechanical Engineering, 2025)
This study examines unsteady heat transfer in the soil mass surrounding an inclined access mine working. Initially, the soils are considered frozen, but due to contact with warmer air entering the mine during summer, they undergo seasonal thawing. The primary challenge in the calculation of heat transfer is the loosening of soils near the upper boundary of the freezing front, caused by thaw consolidation—an effect particularly common in water-saturated, fine-grained soils. This phenomenon affects both the propagation rate of the pore moisture phase transition front and the stability of frozen soils in this zone. A bond-based peridynamic approach is employed to model heat transfer throughout the frozen and thawing soils surrounding the mine, using a case study of seasonal thawing near an access working in a mine located in the Republic of Yakutia. Numerical simulation was conducted using integral equations describing particle interactions within a finite influence region. The loosening zone is calculated using a simplified solution of the peridynamic motion equation. Model verification was performed to ensure the independence of the solution from numerical method parameters. The temporal evolution of thawing zone depth was analyzed for various thermal properties of the soil. For the first time, it has been demonstrated that thaw consolidation significantly affects the temperature field in soils surrounding a mine working.